Open Polar – a global open access portal to research on the polar regions - Dijkstra, Noortje; Abu-Alam, Tamer; Aspaas, Per Pippin; Figenschou, Lars; Longva, Leif; Nilsen, Karl Magnus; Odu, Obiajulu (2021)
Poster presentation at the Svalbard Science Conference 2021, Fornebu, 02.11.21 - 03.11.21, arranged by Research Council of Norway. https://www.forskningsradet.no/en/svalbard-science-forum/ssf-tools-and-funding-schemes/svalbard-science-conference/. Research activities and research output, in general, have increased, and keep increasing vastly, and so too is research on the polar regions including Svalbard in the Arctic. Major commercial publishers have built subscription-based services which present research literature for a fee. As Open Science and open access to literature and data is gaining momentum, there is a distinct need for powerful discovery tools that can harvest and present research literature and datasets in open access form - free of charge. Moreover, sharing of underlying data in open access form is becoming the new norm. So, to integrate research papers and datasets in the same search, helps speed up the discovery processes as well as fostering the transparency of research, and minimize duplication of fieldwork and experiments. Open Polar (https://openpolar.no/) is developed by UiT The Arctic University of Norway, and is a free to use discovery tool for open access publications and research data specifically targeting research output on the polar regions, across all subject areas, and irrespective of where the research originates. Through a carefully designed algorithm, Open Polar is extracting metadata (including URL to the landing page of the full text) from more than 4600 sources worldwide and making these accessible through a user-friendly search service - including an option to search via geolocations on a map, and with systematic search features. The algorithm used picks up relevant research located in the most remote content providers and sources. Thus, searching in Open Polar will result in records purely of relevance to the polar regions. In this contribution, we will present the many advantageous features of Open Polar, and show how Open Polar is supporting Open Science and research ...